2014
DOI: 10.1371/journal.pone.0100809
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, In Vitro Release and Degradation of Cathelicidin-BF-30-PLGA Microspheres

Abstract: Cathelicidin-BF-30 (BF-30), a water-soluble peptide isolated from the snake venom of Bungarus fasciatus containing 30 amino acid residues, was incorporated in poly(D,L-lactide-co-glycolide) (PLGA) 75∶25 microspheres (MS) prepared by a water in oil in water W/O/W emulsification solvent extraction method. The aim of this work was to investigate the stability of BF-30 after encapsulation. D-trehalose was used as an excipient to stabilize the peptide. The MS obtained were mostly under 2 µm in size and the encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…There are two major signalling pathways in the process of apoptosis: one is the death receptor ligand signalling pathway, which is the ligand binding with the receptor of cell membrane to active various apoptotic precursors, thereby inducing apoptosis, and the other is the mitochondrial signalling pathway, which is disrupting mitochondrial structure and function, promoting apoptosis molecules to make the mitochondria release cytochrome into the cytoplasm and influencing a range of biological properties of cell so as to die . Regulating the expression of apoptosis‐related proteins can induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major signalling pathways in the process of apoptosis: one is the death receptor ligand signalling pathway, which is the ligand binding with the receptor of cell membrane to active various apoptotic precursors, thereby inducing apoptosis, and the other is the mitochondrial signalling pathway, which is disrupting mitochondrial structure and function, promoting apoptosis molecules to make the mitochondria release cytochrome into the cytoplasm and influencing a range of biological properties of cell so as to die . Regulating the expression of apoptosis‐related proteins can induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al previously demonstrated that native BF-30 may selectively inhibit the proliferation of melanoma cells via in vitro permeabilization of cytoplasmic membrane and DNA-binding, and exerted the outstanding anti-cancer effects in B16F10-bearing mice 4 . However, native BF-30 was restricted in a short lifespan which mainly caused by the rapid glomerular filtration and protease digestion 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging resistance to colistin and tigecycline, two of the few choices for last-resort treatment of P. aeruginosa and A. baumannii , may make this situation worse (Cai et al, 2012 ; Deng et al, 2014 ; Potron et al, 2015 ; Lee et al, 2016 ). Some antimicrobial peptides (AMPs) have shown excellent effects on these drug-resistant pathogens in vitro but are not able to be administered systemically due to their shortcomings, such as hemolytic activity or poor stability in vivo (Ramamoorthy et al, 2006 ; Zetterberg et al, 2011 ; Vila-Farres et al, 2012 ; Li et al, 2014 ; Liu et al, 2015 ). Though efforts have been made, mainly based on structural design, to overcome these disadvantages, no AMP is clinically available to date (Fjell et al, 2011 ; Andres, 2012 ).…”
Section: Introductionmentioning
confidence: 99%